2021
DOI: 10.1007/s40211-020-00384-4
|View full text |Cite
|
Sign up to set email alerts
|

Zur Komorbidität von Posttraumatischer Belastungsstörung und Sucht in biopsychosozialer Perspektive

Abstract: ZusammenfassungPosttraumatische Belastungsstörung und Substanzkonsumstörungen treten im medizinischen Versorgungssystem häufig koexistent auf. Ihre Komorbidität geht mit schwerwiegenderen akuten klinischen Symptombildern, mit zahlreichen, oft notfallmäßigen Hospitalisierungen und geringeren Behandlungserfolgen einher. Ihre Komorbidität trägt zu dramatisch ungünstigeren Verläufen auf allen biopsychosozialen Ebenen bei. Das Thema Komorbidität von PTBS und Sucht wird auf mehreren Ebenen untersucht: in den Perspek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 204 publications
(238 reference statements)
0
2
0
Order By: Relevance
“…First, a common biological dysfunction or vulnerability might increase the likelihood to develop either disorder in the course of their life [ 9 ] (given the appropriate environmental variables, such as a traumatic events), as indicated by data showing that both disorders have a similar age of onset, namely around adolescence [ 10 ]. Accordingly, some studies have found genetic markers that are related to PTSD as well as SUD, such as polymorphism of the GABA receptor [ 11 13 ]. Second, circumstances promoting development of SUD in adolescents often include adverse life events or traumatic experiences (TEs) [ 14 ], and this increased exposure to TEs might also facilitate the development of PTSD [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, a common biological dysfunction or vulnerability might increase the likelihood to develop either disorder in the course of their life [ 9 ] (given the appropriate environmental variables, such as a traumatic events), as indicated by data showing that both disorders have a similar age of onset, namely around adolescence [ 10 ]. Accordingly, some studies have found genetic markers that are related to PTSD as well as SUD, such as polymorphism of the GABA receptor [ 11 13 ]. Second, circumstances promoting development of SUD in adolescents often include adverse life events or traumatic experiences (TEs) [ 14 ], and this increased exposure to TEs might also facilitate the development of PTSD [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several adverse effects of substance abuse on the consumers themselves and the social context in which they live. These include physical and mental comorbidities as well as psychosocial and social difficulties 3–7. Regarding the societal impact of substance abuse, these physical and psychological consequences cause substantial economic and social burdens, for example, early retirement 8 9.…”
Section: Introductionmentioning
confidence: 99%